2010
DOI: 10.1103/physrevb.81.035211
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the character of ferromagnetic Mn in epitaxial Fe/(Ga,Mn)As heterostructures

Abstract: We demonstrate that the growth of Fe/͑Ga,Mn͒As heterointerfaces can be efficiently controlled by epitaxy and that robust ferromagnetism of the interfacial Mn atoms is induced at room temperature by the proximity effect. X-ray magnetic circular dichroism and x-ray resonant reflectivity data, supported by theoretical calculations, were used to monitor both temperature and magnetic field dependence of the Mn magnetic moment in the semiconducting host. We identify distinct Mn populations, each of them with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
4
15
3
Order By: Relevance
“…4(d)] and one order of magnitude smaller for Fe/30 nm (Ga,Mn)As with 6% Mn. The evidence of ferromagnetic exchange bias is seemingly in contrast to our observation of an antiparallel alignment (thickness (Ga,Mn)As 15 nm) of the two layers at the interface 12,13 and to the observation of an antiferromagnetic exchange bias effect in recent SQUID measurements of Fe/(Ga,Mn)As bilayer samples.…”
Section: B Magnetometrycontrasting
confidence: 99%
See 3 more Smart Citations
“…4(d)] and one order of magnitude smaller for Fe/30 nm (Ga,Mn)As with 6% Mn. The evidence of ferromagnetic exchange bias is seemingly in contrast to our observation of an antiparallel alignment (thickness (Ga,Mn)As 15 nm) of the two layers at the interface 12,13 and to the observation of an antiferromagnetic exchange bias effect in recent SQUID measurements of Fe/(Ga,Mn)As bilayer samples.…”
Section: B Magnetometrycontrasting
confidence: 99%
“…The presence of a clear Mn magnetic signal at room temperature indicates that a small part of the (Ga,Mn)As layer, located at the interface, exhibits ferromagnetic order due to the proximity effect of the Fe layer, as already observed in previous experiments. [12][13][14] In Fig Even though the magnitude and the shape of the XMCD of Fe and Mn is in perfect agreement with previous studies the sign of the coupling between the Fe and Mn is opposite to the one observed so far. In fact, an antiparallel alignment has always been observed at the Fe/(Ga,Mn)As interface, while the up-down feature of the XMCD of Fe and Mn in Figs.…”
Section: A X-ray Magnetic Circular Dichroismsupporting
confidence: 89%
See 2 more Smart Citations
“…This is due to the enhanced, conduction-electron-mediated RKKY coupling between the Eu 4f spins [8,9]. In thin films and interfaces these fundamental magnetic properties can also be influenced by additional factors, such as surface-induced modification of the crystalline environment and of the band structure [10] as well as magnetic proximity effects [11][12][13]. These interface effects have been studied experimentally mainly in 3d systems, be they itinerant ferromagnets [10] or transition metal oxides [14,15], while interfaces of the 4f compound EuO have only been analyzed theoretically [16,17].…”
mentioning
confidence: 99%